Surgical Outcomes of Carpal Tunnel Syndrome in Rheumatologic Patients - Yusuf Kıratlıoğlu; Uğur Bezirgan (Ankara Üniversitesi Tıp Fakültesi Mecmuas, 2025)
Objectives: Carpal tunnel syndrome (CTS) is a common condition that often coexists with rheumatologic diseases, leading to significant functional impairment and reduced quality of life. This study aimed to evaluate the outcomes of open decompression surgery for CTS in individuals with rheumatologic diseases, focusing on symptom severity and functional status improvements. Materials and Methods: A retrospective analysis was conducted on 27 patients diagnosed with CTS and concomitant rheumatologic diseases. These patients underwent open decompression surgery under local anesthesia between January 2021 and June 2023. Outcomes were assessed using the Boston symptom severity scale (BSSS) and the Boston functional status scale (BFSS) preoperatively and at follow-up appointments postoperatively. Results: Postoperative evaluations revealed significant improvements in both BSSS and BFSS scores. Patients reported marked relief in symptom severity and improvements in their ability to perform daily activities. These improvements were consistent across the cohort, indicating the reliability of surgical intervention. Conclusion: The findings suggest that open decompression surgery is an effective and reliable method for managing CTS symptoms in patients with rheumatologic diseases. This surgical approach not only alleviates symptom severity but also enhances functional capabilities, contributing to a better quality of life.